Peran Syekh Abdullah Mubarok Dalam Penyebaran Tarekat Qadiriyah Naqsyabandiyah Di Priangan, 1900-1940an - Angga Pusaka Hidayat (Jurnal Tamaddun, 2022)
This paper intends to explain how a tarekat was spread. The approach used to explain the spread of the Tarekat Qadiriyah Naqsyabandiyah in Priangan in 1900-1940s was actor oriented. The central figure in the effort to spread the tenets of this tarekat is Syekh Abdullah Mubarok, the mursyid and founder of the Pesantren Suryalaya. There are four main elements discussed in relation to efforts to spread the tenets of the tarekat, namely leader and leadership, goal orientation, political teams, and strategies to achieve goals. The research method used is the historical method which consists of heuristic, criticism, interpretation, and historiography. The results of this study explain that in the actor oriented perspective, the spreading of the Tarekat Qadiriyyah Naqsyabandiyyah in in Priangan was due to the success of its leader and political team in expanding and tightening the network and their success in playing strategies and maneuvers that ultimately force opposing parties to lower his aspirations. The figure of Syekh Abdullah Mubarok, his attitude and strategy, as the leader of the tarekat, plays an important role in the effort to spread this teaching.